Molecular Structure, Vibrational Spectroscopic (FT-IR, FT-Raman),UV-Vis Spectra, First Order Hyperpolarizability, NBO Analysis, HOMO and LUMO Analysis, Thermodynamic Properties of 2,6-Dichloropyrazine by Ab Initio HF and Density Functional Method (Journal of Atomic and Molecular Sciences, 2013)
FT-IR and FT-Raman spectra of 2,6-dichloropyrazine were recorded and analyzed. The vibrational wavenumbers were examined theoretically using DFT/B3LYP /6-311G(d,p) level of theory. The data obtained from vibrational wavenumber calculations are used to assign vibrational bands obtained in infrared spectroscopy of the studied molecule. The calculated first hyperpolarizability is comparable with the reported values of similar derivatives and is an attractive object for future studies of non-linear optics. The assignments of the vibrational spectra have been carried out with the help of normal coordinate analysis (NCA) following the Scaled Quantum Mechanical Force Field Methodology (SQMFF). UV-visible spectrum of the title molecule has also been calculated using TD-DFT/6-311G(d,p) method. The calculated energy and oscillator strength  exactly reproduces reported experimental data. The Mulliken population analysis on atomic charges and the HOMO-LUMO energy are also calculated.